Efficiency Of Physicochemical Methods In Assessing The Quality Of Canned Products - Khamraqulova Muborak Khakimovna; Rustamjonov Azizbek Nodirjon ogli (Academia One Publishing, 2025)
This article explores the effectiveness of physicochemical methods in evaluating the quality of canned food products. In the context of growing food safety requirements and increasing consumer demands, precise and reliable assessment techniques are essential. The study focuses on determining key parameters such as pH level, total soluble solids (TSS), titratable acidity, and the presence of preservatives or contaminants. By comparing traditional sensory analysis with instrumental physicochemical techniques, the research highlights the advantages of modern laboratory diagnostics in ensuring the stability, nutritional value, and compliance of canned goods with regulatory standards. The results demonstrate that physicochemical approaches offer higher objectivity, reproducibility, and sensitivity in quality assessment processes
Keywords: Canned product; physicochemical methods; food quality